Analisis Perbandingan Transaksi Tunai dan No Tunai Gerbang Tol Cikarang Utama pada PT Jasa Marga (PERSERO) Tbk - Adenan Suhalis; Herliana Handayani; Aang Gunawan (Institut Transportasi dan Logistik Trisakti, 2018)
PT. Jasa Marga (Persero) Tbk is one of the highway service providers in Indonesia. The company has already been trusted to take the responsibility in building a number of highways in Indonesia. The objective of this research is to figure out the number of vehicles’ queues at Cikarang Utama Toll gate. The method applied in this research were field observation, unstructured interview, library research, and company data taken. From the result of the analysis, it can be seen that the service time of cash transaction in each toll booth at Cikarang Utama Toll gate is 11,11 second/ vehicle. The number of vehicles passing Cikarang Utama Toll gate are 2449 vehicles. The service time of non-cash transaction at Cikarang Utama Toll gate is 8,92 second/ vehicle. The number of vehicles passing Cikarang Utama toll gate within 1 hour using non-cash transaction is 2660 vehicles. The time difference between those two transactions is 2,19 second/ vehicle. The difference in number of vehicle passing the Toll gate within 1 hour is 211 vehicles.